A PHONOLOGICAL PROBLEMS AND ERRORS OF STUDENTS PRONOUNCIATION IN READING ENGLISH TEXT AT ENGLISH DEPARTMENT OF UNIVERSITY HKBP NOMMENSEN - Silvina Yuliana L. Tobing; Kammer Sipayung; Carolina Pakpahan (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
" A Phonological Problems and Errors of Students Pronunciation in Reading English Text at English Department of University HKBP Nommensen". English Language Education Program, Faculty of Teacher Training and Education. HKBP Nommensen University Medan.This study aims to find out the pronounciation problems and pronunciation errors made by students semester sixth group B at English Department of University HKBP Nommensen Medan. Researcher used a qualitative descriptive method. The data of this study are transcript of students pronunciation recording in English short story text. There were 15 students at English Department who were taken randomly. The data were analyzed based on (Ladefogeds, 2001) theory to look for types of pronunciation errors using phonetic transcript, data collection was done through voice recordings and the Elsa speak application. The results showed that students made the following muel pronunciation mistakes [?, ?, ?, ?:,]. The total pronunciation errors in vowel sounds are 40 errors. The errors consist of 18 omission errors, 6 addition errors and 16 msinformation errors. Vowel pronunciation mistakes made by students can be caused by several factors, for example the influence of the first mother tongue (interference), the influence of the second language learned (overgeneralization), and the influence of developmental errors.